STUDI EKSPLORATORI TERHADAP SEGMENTASI SERTA ATRIBUT METROSEKSUAL TERHADAP JASA SALON (Studi Kasus : Pria Metroseksual di Jakarta) - Lenggogeni, Sari (Universitas Muhammadiyah Magelang, 2007)
A new segment so called Metrosexsual is an emerging issue in the marketng?s world today. They has been widespread appeared in most of big cities over the world. They are know as narcist guy, hedonic and mostly find themselves as a customer of beauty salon services. These males mostly found themselves in the following characters : they tend to have intensive treatment in fitness cener, social butterfly, fashion oriented. These phenomenon is a potential marke for beauty salon service which provide several treatment to support their lifestyle. Based on the needs to explore some characters both in demographic also pshyycographic segmentation, further to dig informations about beauty salon attributes toward metrosexual importance, a research using judgmental sampling method was conducted amongst 100 males respondents judged as metrosexual segment in Jakarta. This study aims to find out how the metrosexual behave in the term of a beauty salon services customer, to this service?s attributes. The result shows that there are 11 attributes affect decision of metrosexual segment in term of selecting beauty salon services. The demographic segmentatin shows that majority of men aged 20-19 years old, unmarried, student and private sector employees were the biggest group amongst overall respondent, meanwhile, pshycographic segmentation were divided up into three groups, namely ; the happy active man, conventional, and trend follower.